Cost minimization and budget impact analysis of the use of a new 6-month form of triptorelin in the treatment of patients with prostate cancer in Ukraine - S. O. Soloviov; E. O. Stakhovsky; M. V. Leleka; F. V. Hladkykh (The State Expert Center of the Ministry of Health of Ukraine, 2022)
Prostate cancer is one of the most serious health problems encountered by the manhood of different countries of the world. Prostate cancer is a hormone-dependent tumor - growth and proliferation of both normal and cancer cells significantly depend on level of androgens. The analogues of gonadotropin-releasing hormone have been widely applied in prostate cancer therapy for more than 15 years. In Ukraine goserelin (1 month, 1 M; 3 months, 3 M) currently occupies the major part of market among the analogues of gonadotropin-releasing hormone. The alternative to goserelin is triptorelin (1 month, 1 M; 1 months, 3 M; 6 months, 6 M) - another well-studied and widely applied analogue of gonadotropin-releasing hormone, which is used for medical castration in cases of prostate cancer. Taking this into consideration, conducting the analysis of triptorelin and goserelin application is relevant. The purpose of the work was to conduct cost minimization and budget impact analysis using triptorelin 6 M and goserelin 3 M in hormonal therapy of prostate cancer in Ukrainian patients. The research was based on treatment cost of one patient during one year under condition of equivalent efficacy and safety of goserelin and triptorelin. The pharmacoeconomic analysis was conducted according to the «cost minimization» method. For calculation of direct costs when applying goserelin and triptorelin a pharmacoeconomic decision tree model was used, according to which the costs are computed with an allowance for possibilities and expenditures on side effects. The results of pharmacoeconomic modeling showed a tendency for a yearly cost cut in the amount of 2 887.69 UAH per patient when using triptorelin in model cohort which consisted of 1 000 patients. Besides, it allows 137 additional patients per thousand of them to be treated with triptorelin. As the result of modeling the influence on budget it was estimated that the amount of cost saving on buying triptorelin would average at 4,6 million UAH per every year for five years of its implementation. Hormone therapy with application of the analogues of gonadotropin-releasing hormone is one of the major treatment methods of patients with prostate cancer. A pharmacoeconomic analysis of triptorelin application in comparison with goserelin for treating patients with prostate cancer in Ukraine was conducted. The results of pharmacoeconomic modeling showed that a significant cost cut is expected when using triptorelin. It will allow additional patients, who need hormone therapy, to be treated.